Evaluating the Trend of VRE carriages in Health Facilities: A Retrospective Study from 2019-2022 - Cremona, A.; Bordino, V.; Vicentini, C.; Morandi, M.; Vecchietti, R. G.; Zotti, C.M. (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Healthcare-associated infections (HAIs) and multidrug resistance (MDR) are a growing public health threat and pose a risk to patient safety in healthcare facilities. Vancomycin-resistant Enterococci (VRE) are responsible for nosocomial infections and have intrinsic and acquired resistance to many antibiotics, including glycopeptides. VRE carriage can remain undetected, increasing the risk of contact transmission. Identifying colonized patients is crucial for the implementation of preventive measures. Aims. The aims of this study were to evaluate the trend of VRE carriage based on rectal swab results between 2019 and February 2022 in a large Italian trust and the percentage of patients with VRE colonization at the time of hospitalization. Methods. This was a retrospective observational study based on results of rectal swabs performed for screening on admission between January 2019 and February 2022 in four hospitals part of a single trust in Turin, North-Western Italy. The study collected data on the date of specimen collection, type of specimen, isolated pathogen and the date of hospital admission. Descriptive analysis of data was performed, and duplicate samples were not considered. Results. From January 2019 to February 2022 we collected 5025 rectal swabs performed in hospitals of the trust, of which 3037 were performed in 2019 (60%), 741 in 2020 (15%), 611 in 2021 (12%) and 636 in the first two months of 2022 (13%). VRE positivity was found in 162 (3%) rectal swabs, of which 2 cases in both 2019 (0.1%) and 2020 (0.3%), 95 in 2021 (15.5%) and 63 in the first two months of 2022 (9.9%). Furthermore, 52% (84/162) of positive rectal swabs were performed at admission, whereas the remaining 48% (78/162) of positive rectal swabs were performed after 48h. Conclusions. This study found an increasing trend of VRE carriage in the study population during the SARSCoV-2 pandemic, highlighting the importance of screening patients for VRE carriage to prevent worsening clinical conditions, environmental contamination, and prolonged hospitalization.